Grmičev dialoški duh v pokoncilskem ekumenizmu - Krajnc-Vrečko, Fanika (Časopis za zgodovino in narodopisje, 2023)
The discussion highlights Grmič’s dialogical spirit, which is evident in his views on ecumenism and his efforts towards finding a way forward in ecumenical dialogue. Grmič sees ecumenism as an opportunity for communication and dialogue between representatives of various Christian churches. He believes that everyone involved in the dialogue should be considered as equal partners, sharing the search for truth through different paths, but towards the same goal and the same God.
Keywords: ekumenizem; Grmič, Vekoslav; teološka antropologija; vera